The effect of board size and composition on bank efficiency. (30th November 2010) - Agoraki, Maria-Eleni K.; Delis, Manthos D.; Staikouras, Panagiotis K.
This paper analyses the relationship between board structure, in terms of board size and composition, and bank performance in terms of both cost and profit efficiency. Unlike previous studies, the present analysis is carried out within a stochastic frontier framework, while we use a suitable econometric model to solve the well-known endogeneity problem in corporate governance literature. The empirical framework is applied to a panel of large European banks operating during the period 2002-2008. The paper documents a negative correlation between board size, on the one hand, and cost and profit efficiency, on the other hand, while also casts doubt on the conventional regulatory wisdom favouring boards dominated by non-executive directors. Smaller board structures are also associated with better bank efficiency through better management of credit risk. Moreover, we find that dual board systems enhance efficiency, by contrast to increased ownership concentration which seems to exert an insignificant influence. Finally, we identify a positive impact of market discipline upon bank efficiency and report a negative association between bank efficiency and augmented supervisory power as well as foreign ownership.